Pembelajaran Online Menggunakan Aplikasi Google Classroom Padamata Kuliah Matematika MI - Lyna Yuni Artika (LPPM Institut Al-Ma`arif Way Kanan Lampung, 2021)
ABSTRACT Thisis a qualitative research aims to obtain an overview of the implementation online learning using google classroomof basic mathematics class for prospective primary school teacher in Madrasah Ibtidaiyah (PGMI), Tarbiyah department at STAI Al-Ma'Arif Way Kanan as an effort to reflect the provision of lecture materials online.The subject of the study was students of class A a third of PGMI program semester 3. Collected data by the spread of questionnaires through google form.Data analysis was conducted using Miles & Huberman interactive analysis technique.The results showed that: (1) Some students already had the basic facilities needed to follow online learning usingsgoogle classroom; (2) online learning which is using google classroom has flexibility in its implementation and it is able to encourage the emergence of learning independence and motivation to be more active in learning basic Mathematics class.